UPAYA MENINGKATKAN KEMAMPUAN BERBICARA MELALUI BERMAIN PESAN BERANTAI PADA KELOMPOK B1 TK PEMBINA NEGERI 1 KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Nurbani Nurbani; Daviq Chairilsyah; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The background of this study is the lect of ability to speak of children aged 5-6 in the group B1TK Pembina Negeri Kabupaten Rokan Hilir. The words were spoken less precise and less smooth, quiet child if given the questions and the child is less able to repeat the word / phrase being delivered, then there is a child less able to convey the message / information correctly. The purpose of this study was to determine the child's ability to speak through play chain messages, how to play the message chain, then to determine the increase in the ability to speak the child through play chain messages, and the high increase occurred, particularly in children B1 group Pembina State Tk 1 districts Bangko district Rokan Hilir. This research is a classroom action research (PTK), which consists of four basic components: planning, action, observation or observation and reflection. The study was conducted in two cycles. In the first cycle, three meetings and in Cycle II also three meetings.From the results of the acquisition of data analysis with a comparison between the prior cycle (Prasiklus) to the first cycle with a percentage of 25.76%.Comparison between Cycle I and Cycle II by 51.21% as well as a comparison between before Cycle to Cycle II an increase of 95.21%. From the results of research and discussion, it can be concluded that the child's speech can be improved through playing the message chain.Keywords: Speech, Play Message chain